스탠다드 국화 ‘신마’의 잎과 꽃잎 조직 배양시 식물생장조절물질이 신초 및 뿌리형성에 미치는 영향 - 이종숙(Jong Suk Lee); 이긍주(Geung-Joo Lee); 정성진(Sung Jin Chung); 김진백(Jin-Baek Kim); 김동섭(Dong Sub Kim); 강시용(Si-Yong Kang) (Weon'ye gwahag gi'sulji, 2008)
본 연구는 스탠다드 국화 ‘신마’의 잎과 꽃잎 배양을 통해 효율적인 배양조건을 확립하고자 하였다. 배양시작 21-28일 후 신초와 뿌리가 형성되었다. MS배지를 기본으로 하여 BA와 NAA를 조합한 7가지 배지조성 중 잎 배양의 경우 신초 형성률은 0.5mg L-1 BA와 1.0mg L-1 NAA 배지조성에서, 뿌리는 0.1mg L-1 BA와 0.5mg L-1 NAA 배지조성에서 가장 좋았으며, 이와는 달리 꽃잎 배양의 경우 신초는 0.5mg L-1 BA와 0.5mg L-1 NAA로 조합한 배지조건에서, 뿌리는 0.1mg L-1 BA와 1.0mg L-1 NAA 배지 조합조건에서 형성률이 가장 좋았다. 본 연구 결과 같은 품종의 국화라도 배양하는 잎과 꽃잎에 따라 신초 형성에 효율적인 배지 조성이 다른 것을 확인하였고, 캘러스 단계를 거치지 않고 바로 신초를 형성하여 재분화체를 얻는 시간을 단축할 수 있었다. 실험에서 얻어진 결과는 스탠다드 국화 ‘신마’를 이용하여 몇 가지 형질개선을 위한 목적을 위해 방사선 등을 활용한 돌연변이체 유기 시에 대량의 재분화체를 확보하기 위한 중요한 정보로 활용될 수 있을 것으로 기대된다. In this study we investigated the conditions of a higher frequency for regenerated plants from different explants of a standard-type chrysanthemum ‘Jinba’. In vitro culture was initiated on an MS medium containing 3% sucrose, 0.8% agar, and 5 μM benzyl adenine (BA) with naphthalene acetic acid (NAA) by using surface-sterilized leaf and flower tissues from greenhouse-grown plants. Direct shoot regeneration from the leaf and flower explants was obtained 21 to 28 days after the initial culture. Among the seven combinations of the growth regulators used for the culture, the most efficient condition for the shoot and root formation from the leaf tissue was obtained when the MS basic medium was supplemented with 0.5 mg L-1 BA and 1.0 mg L-1 NAA, and 0.1 mg L-1 BA and 0.5 mg L-1 NAA, while the culture using floret tissues was most efficient on the medium supplemented with 0.5 mg L-1 BA and 0.5 mg L-1 NAA, and 0.1 mg L-1 BA and 1.0 mg L-1 NAA. These results will provide valuable information to help set up an efficient system for a tissue culture of chrysanthemum cv. Jinba to improve one or some of its negative traits in combination with a radiation mutagenesis approach. KCI Citation Count: 6